Proceedings of the International Naval Engineering Conference and Exhibition (INEC) 2018
DOI: 10.24868/issn.2515-818x.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

Network-based metrics for assessment of naval distributed system architectures

Abstract: The architecture of a system is generally established at the end of the conceptual design phase where sixty to eighty percent of the lifetime system costs are committed. The architecture influences the system’s complexity, integrality, modularity and robustness. However, such properties of system architecture are not typically analytically evaluated early on during the conceptual process. System architectures are defined using qualitative experience, and the early stage decisions are subject to the judgement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This robustness metric is appropriate for any network where the ability to communicate between well-separated nodes is of paramount importance. A detailed description of the robustness metric is presented in the previous works of Paparistodimou et al (2018Paparistodimou et al ( , 2020. In short, sources and sinks are identified in the DSM, and the level of connectivity between sources and sinks is measured after a disruption.…”
Section: Robustness Metric and Methodsmentioning
confidence: 99%
“…This robustness metric is appropriate for any network where the ability to communicate between well-separated nodes is of paramount importance. A detailed description of the robustness metric is presented in the previous works of Paparistodimou et al (2018Paparistodimou et al ( , 2020. In short, sources and sinks are identified in the DSM, and the level of connectivity between sources and sinks is measured after a disruption.…”
Section: Robustness Metric and Methodsmentioning
confidence: 99%
“…(Pouw, 2007), (van Oers, 2011), (de Vos, 2018 and (Habben Jansen et al, 2020). Related research for other applications can be found in (Paparistodimou, 2018) and (Huisman, 2015). In the work presented in this article the fundamental idea is that ship designers and marine engineers can be supported during early-stage naval ship design as well, by having a 'tool' that generates concept designs for naval power plants.…”
Section: Design Space Of Naval Power Plant Concept Exploration Toolmentioning
confidence: 99%
“…The notion that a function can be satisfied if a set of source and sink components of the flow network maintain sufficient connectivity after a disruption is accepted in order to formulate the robustness evaluation indicator metric. The following paragraphs present the robustness evaluation indicator metric which is an updated version from an earlier formulation developed by Paparistodimou et al (2019).…”
Section: Robustness Evaluation For Given Redundancy Modularity and Dmentioning
confidence: 99%